A novel TLR2‐triggered signalling crosstalk synergistically intensifies TNF‐mediated IL‐6 induction. Issue 7 (24th April 2014) - Chang, Yu‐Ling; Chen, Tzu‐Hui; Wu, Yi‐Hsiu; Chen, Guann‐An; Weng, Tzu‐Huei; Tseng, Ping‐Hui; Hsieh, Shie‐Liang; Fu, Shu‐Ling; Lin, Chi‐Hung; Chen, Chun‐Jen; Chu, Ching‐Liang; Chio, Iok In Christine; et al.
Abstract Toll‐like receptors (TLR) recognize pathogens and trigger the production of vigorous pro‐inflammatory cytokines [such as tumour necrosis factor (TNF)] that induce systemic damages associated with sepsis and chronic inflammation. Cooperation between signals of TLR and TNF receptor has been demonstrated through the participation of TNF receptor 1 (TNFR) adaptors in endotoxin tolerance. Here, we identify a TLR2‐mediated synergy, through a MyD88‐independent crosstalk, which enhances subsequent TNF‐mediated nuclear factor‐kappa B activation and interleukin‐6 induction. Membrane‐associated adaptor MAL conduces the link between TNF receptor‐associated factor 6 (TRAF6) and TNFR‐associated death domain, leading to a distinctive K63‐ubiquitinylated TRAF6 recruitment into TNFR complex. In summary, our results reveal a novel route of TLR signal that synergistically amplifies TNF‐mediated responses, indicating an innovative target for inflammation manipulation.